Fibrin deposition on bovine pericardium tissue used for bioprosthetic heart valve drives its calcification - Poitier, Bastien; Rancic, Jeanne; Richez, Ulysse; Piquet, Julie; El Batti, Salma; Smadja, David M. (Frontiers in Cardiovascular Medicine, 2023)
Background Bioprosthetic heart valves (BHVs) are less thrombogenic than mechanical prostheses; however, BHV thrombosis has been proposed as a risk factor for premature BHV degeneration. Objectives We aimed to explore whether fibrin deposition on bovine pericardium tissue could lead to calcification. Method Fibrin clot was obtained by blending three reagents, namely, CRYOcheck™ Pooled Normal Plasma (4/6), tissue factor + phospholipids (Thrombinoscope BV), and 100 mM calcium (1/6), and deposited on pericardium discs. Non-treated and fibrin-treated bovine pericardium discs were inserted into the subcutaneous tissue of 12-day-old Wistar rats and sequentially explanted on days 5, 10, and 15. Calcium content was measured with acetylene flame atomic absorption spectrophotometry. Histological analysis was performed using hematoxylin–eosin staining, Von Kossa staining, and immunohistochemistry. Results Calcification levels were significantly higher in fibrin-treated bovine pericardium discs compared to those in non-treated bovine pericardium discs (27.45 ± 23.05 µg/mg vs. 6.34 ± 6.03 µg/mg on day 5, 64.34 ± 27.12 µg/mg vs. 34.21 ± 19.11 µg/mg on day 10, and 64.34 ± 27.12 µg/mg vs. 35.65 ± 17.84 µg/mg on day 15; p < 0.001). Von Kossa staining confirmed this finding. In hematoxylin–eosin staining, the bovine pericardium discs were more extensively and deeply colonized by inflammatory-like cells, particularly T lymphocytes (CD3+ cells), when pretreated with fibrin. Conclusion Fibrin deposition on bovine pericardium tissue treated with glutaraldehyde, used for BHV, led to increased calcification in a rat model. BHV thrombosis could be one of the triggers for calcification and BHV deterioration.